Adivasis (Original Dwellers) “in the way of” State-Corporate Development: Development dispossession and learning in social action for land and forests in India - Kapoor, Dip (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis paper traces the kinds of learning engendered through Adivasi trans-local and local subaltern social movement (SSM) action addressing state-corporate developmental collusions, state-caste interests and the resulting dispossession of Adivasis from land, forest and their ways of life given the economic liberalization drive to exploit resources in the rural hinterlands in India since 1991. The paper draws upon insights from the author’s association with the Adivasi since 1992 and funded research into “Learning in Adivasi movements.”